Twenty novel mutations in the alpha-galactosidase A gene causing Fabry disease. - Topaloglu, A. K. (The Feinstein Institute for Medical Research, 1999)
BACKGROUND: Fabry disease, an X-linked inborn error of glycosphingolipid catabolism, results from the deficient activity of the lysosomal exoglycohydrolase alpha-galactosidase A (EC 3.2.1.22; alpha-Gal A). The nature of the molecular lesions in the alpha-Gal A gene in 30 unrelated families was determined to provide precise heterozygote detection, prenatal diagnosis, and define genotype-phenotype correlations. MATERIALS AND METHODS: Genomic DNA was isolated from affected males and/or carrier females from 30 unrelated families with Fabry disease. The entire alpha-Gal A coding region and flanking intronic sequences were analyzed by PCR amplification and automated sequencing. RESULTS: Twenty new mutations were identified, each in a single family: C142R, G183D, S235C, W236L, D244H, P259L, M267I, I289F, Q321E, C378Y, C52X, W277X, IVS4(+4), IVS6(+2), IVS6(-1), 35del13, 256del1, 892ins1, 1176del4, and 1188del1. In the remaining 10 unrelated Fabry families, 9 previously reported mutations were detected: M42V, R112C, S148R, D165V, N215S (in 2 families), Q99X, C142X, R227X, and 1072del3. Haplotype analysis using markers closely flanking the alpha-Gal A gene indicated that the two patients with the N215S lesion were unrelated. The IVS4(+4) mutation was a rare intronic splice site mutation that causes Fabry disease. CONCLUSIONS: These studies further define the heterogeneity of mutations in the alpha-Gal A gene causing Fabry disease, permit precise heterozygote detection and prenatal diagnosis, and help delineate phenotype-genotype correlations in this disease. </AB